Pengaruh Risiko Perbankan dan Faktor Ekonomi Makro terhadap Disiplin Pasar: Studi pada Perbankan Konvensional di Indonesia Periode 2017 – 2022 - Lukmanul Hakim; Mokhamad Anwar; Layyinaturrobaniyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of banking risk and macroeconomic factors on market discipline in conventional banking in Indonesia during the period 2017 - 2022. Banking risk variables include credit risk represented by the Non Performing Loan (NPL) ratio, liquidity risk measured using the Loan to Deposit Ratio (LDR), and operational risk proxied through the ratio of Operating Expense to Operating Income, while macroeconomic variables include the inflation rate and BI rate. Market discipline is proxied by the growth of Third Party Funds (DPK). The population in this study consisted of banks in Indonesia, while the sample selection used purposive sampling method with a total of 85 conventional banks in Indonesia as samples. This study uses panel data regression analysis method by utilizing secondary data taken from bank financial statements through the Otoritas Jasa Keuangan (OJK) website and macroeconomic data obtained from the Bank Indonesia (BI) website. The results indicate that credit risk and BI rate variables have a significant negative influence on market discipline. However, liquidity risk, operational risk, and inflation rate variables have no influence on market discipline.